Can laboratory-based tennis profiles predict field tests of tennis performance? - Perry, A. C.; Wang, X.; Feldman, B. B.; Ruth, T.; Signorile, J. (The Journal of Strength and Conditioning Research, 2004)
The present study examined the impact of physical characteristics of adolescent competitive tennis players (13-18 years) on field tests of tennis performance. Results (n = 33) showed that boys were taller (p = 0.001), possessed greater wingspan (p = 0.030), had greater maximum oxygen consumption (p = 0.001), and performed better on isokinetic strength measurements. Multiple regression analyses controlling for age and sex showed that height (p = 0.025), maximum minute ventilation (p = 0.005), and isokinetic strength measurements significantly and positively affected ball velocity. Knee extension average power was the only variable to positively and significantly affect ball placement (p = 0.040); however, several isokinetic strength measurements negatively affected ball placement. For the nondominant side, down-the-line strokes showed reduced accuracy (p = 0.001) and ball velocity (p = 0.001) compared with cross-court strokes. Given our results, resistance training may be beneficial for the performance of on-court tennis play.